2020
DOI: 10.1186/s13054-020-2744-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cisatracurium infusion on the energy expenditure of critically ill patients: an observational cohort study

Abstract: Background: Both overfeeding and underfeeding of intensive care unit (ICU) patients are associated with worse outcomes. A reliable estimation of the energy expenditure (EE) of ICU patients may help to avoid these phenomena. Several factors that influence EE have been studied previously. However, the effect of neuromuscular blocking agents on EE, which conceptually would lower EE, has not been extensively investigated. Methods: We studied a cohort of adult critically ill patients requiring invasive mechanical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…We found observed changes in mREE do not demonstrate a significant relationship to organ failure severity and are only minorly affected by prone positioning/paralysis, as over the study period the use of these therapies was not significantly different. This is consistent with previously published data showing that paralysis appears to have only a minor effect on mREE 39 . Our data strongly suggest that personalization of nutrition delivery via routine, longitudinal IC use 1,34 should be considered as the new standard of care to accurately assess EE, help guide nutrition therapy in COVID‐19 (and, likely, other ICU patients), and improve patient care overall.…”
Section: Use Of Ic In Covid‐19 Icu Patientssupporting
confidence: 91%
“…We found observed changes in mREE do not demonstrate a significant relationship to organ failure severity and are only minorly affected by prone positioning/paralysis, as over the study period the use of these therapies was not significantly different. This is consistent with previously published data showing that paralysis appears to have only a minor effect on mREE 39 . Our data strongly suggest that personalization of nutrition delivery via routine, longitudinal IC use 1,34 should be considered as the new standard of care to accurately assess EE, help guide nutrition therapy in COVID‐19 (and, likely, other ICU patients), and improve patient care overall.…”
Section: Use Of Ic In Covid‐19 Icu Patientssupporting
confidence: 91%
“…To our knowledge, this is the first description of longitudinal mREE in a COVID-19 ICU population. The COVID-19 metabolic phenotype may be unique from previously described ICU models of metabolic response [2], with a more prolonged hypermetabolic phase that may be independent of severity of organ failure and, as previously published, may only be minorly affected by interventions such as paralysis [6]. Further, it is one of the largest single-ICU diagnosis cohorts with longitudinal IC measures for 21 days.…”
mentioning
confidence: 81%
“…Sedatives and analgesics may cause reductions in VO 2 and REE [ 4 , 13 ]. Neuromuscular blocking agents also affect the EE, although the effect is small [ 8 , 24 , 28 , 77 , 78 ]. A recent study with continuous infusion of cisatracurium showed a significant reduction in EE measured with the VCO 2 method, although the clinical relevance is presumed to be minor, and in most patients no reductions in caloric prescription are necessary [ 78 ].…”
Section: Indirect Calorimetrymentioning
confidence: 99%
“…Neuromuscular blocking agents also affect the EE, although the effect is small [ 8 , 24 , 28 , 77 , 78 ]. A recent study with continuous infusion of cisatracurium showed a significant reduction in EE measured with the VCO 2 method, although the clinical relevance is presumed to be minor, and in most patients no reductions in caloric prescription are necessary [ 78 ]. Furthermore, the administration of vasopressors increases REE, whereas specific β-blockers are contradictory reported to decrease REE [ 8 , 35 , 77 , 79 ].…”
Section: Indirect Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation